(untitled) (International Journal of Environmental Sciences, 2025)
Background: Adolescence is a period marked by substantial physical, psychological, and emotional changes. Many parents lack the necessary knowledge to effectively support their teenage children through these changes. A comprehensive nursing program can equip parents with crucial knowledge and skills for better parenting during adolescence. Objective: To assess the effect of a comprehensive nursing program on the knowledge regarding adolescent changes and parenting among parents of teenagers Methods: A one-group pretest-posttest pre-experimental design was employed. Fifty parents were selected through non-probability purposive sampling. A structured questionnaire was used to assess knowledge before and after implementation of the comprehensive nursing program. Descriptive and inferential statistics were applied for data analysis. Results: The mean pre-test knowledge score was 9.96 (SD = 2.22), and the mean post-test score was 12.52 (SD = 2.34). A paired t-test value of 31.81 was statistically significant (p < 0.05), indicating effectiveness of the program. No significant association was found between pretest knowledge and demographic variables. Conclusion: The comprehensive nursing program significantly improved the knowledge of parents regarding adolescent changes and parenting. Structured programs should be incorporated in community health and school-based parental guidance services.